Architecture as a reflection of social structure : a reminiscience of the Sulaymaniye Complex of Istanbul - Ibrahim, Mansor; Jahn Kassim, Puteri Shireen; Idris, Mesut; Abd. Latip, Nurul Syala; Zainal Abidin, Norzalifa (Kulliyyah of Architecture & Environmental Design, IIUM and Al-Bukhary Foundation, 2010)
Physical and spatial structure including the hierarchy of spaces and linkages becomes a window into understanding human social relations which governed by social practices of its time. This is because architectural monuments represent a manifestation of those values and practices. The content of this book brings together selected portions of the renowned Süleymaniye complex in Istanbul, Turkey, from an outcome of general historical research project undertaken in ‘Heritage Studies’ activities of the Kullyyyah. Throughout the book, architecture and urban planning is seen as a mirror to the social structure and the social institutions of the Ottoman society at the time. The making of architecture and urban planning to some extent reflected the values and practices underlying these institutions namely the waqf or charitable foundation. Thus an analysis of the Süleymaniye, not only demonstrates the achievements of building technology and construction of the time, but of the success of aims of the waqf. The link is made between the social structure and institutions of the 15th and 16th centuries and the physical patterns in planning, architecture and construction. A work of architecture and urban design become a mean of deepening our understanding of not only architectural language and technical achievements, but of the society, human relations and values which created it.